Examining Contemporary Challenges and Solutions in Audit Practice - Pasolo, Muhammad Ridhwansyah (Advances in Managerial Auditing Research, 2024)
The study explores contemporary challenges and innovative solutions in audit practice, aiming to enhance audit quality and effectiveness in the digital age. The purpose is to examine the multifaceted nature of the audit profession and its dynamic interaction with evolving business landscapes, regulatory frameworks, and technological advancements. Employing a literature review approach, the research design and methodology involve synthesizing insights from scholarly articles and theoretical frameworks to elucidate key themes and trends in audit practice. Findings reveal significant hurdles faced by auditors, including the escalating complexity of financial transactions, regulatory compliance requirements, and the emergence of new technologies. Moreover, innovative solutions such as data analytics, artificial intelligence, continuous auditing, and interdisciplinary collaboration offer promising avenues for addressing these challenges and providing stakeholders with timely assurance and insights into organizational performance. The implications of the study underscore the importance of proactive adaptation, continuous professional development, and collaboration among audit professionals, academia, industry stakeholders, and regulatory bodies in driving innovation, enhancing knowledge sharing, and advancing best practices in the audit profession. The study contributes to the literature by providing insights into emerging audit trends, best practices, and challenges facing the profession, with implications for audit quality, efficiency, and effectiveness in the digital age